ChemInform Abstract: A New Method for Intramolecular Chloroamination of Unfunctionalized Olefins. Issue 30 (4th July 2013) - Liu, Gong‐Qing; Li, Wei; Li, Yue‐Ming
Abstract using CuCl2 as both promoter and chlorine source